Translation of part marking codes in different systems - Petrović, Saša M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Marking of products using defined codes is common practice. Products are designated by producers, traders and consumers. In the case when there is a need for the supply or exchange of products between two different systems, there is a problem of mutual communication. The problem can be solved on a case-by-case basis or systematically, by introducing a new labeling system. Any introduction of new labeling systems is a costly and lengthy process. Thanks to modern software tools, the problem can be overcome in real time, which is an affordable solution, economically and logistically. This paper considers a possibility of the translation of labeling of spare parts in different marking systems.
Keywords: parts marking; Interoperability; codification